A risky treat: exploring parental perceptions of the barriers to seating their children in the rear seats of passenger vehicles. Issue 2 (19th April 2007) - Lennon, Alexia
Abstract : Background: Sitting in the rear seat of a vehicle rather than in the front seat reduces children's risk of injury or death by ⩾35% in the event of a crash. As road trauma is a leading cause of child morbidity and mortality in highly motorised nations, even in countries where restraint use is high, encouraging parents to place children in the rear seats of vehicles offers a low-cost avenue to improving children's overall health. However, little is known about the factors that affect parents' decisions about seating positions. Objective: To explore parental perceptions of barriers to placing their children in the rear seat of passenger vehicles whenever possible. Design and subjects: Focus group discussions were held with urban parent-drivers to elicit their concerns about children's car safety and barriers to rear-seat use. Results: Most parents had a rule that children should sit in the rear seat. Parents said that they relaxed these rules for a variety of reasons including social pressure, perceptions of the trip as short and because children regard sitting in the front seat as a treat. Parenting style, child cooperativeness, social pressure and inability to justify the risk of injury were identified as barriers to rear-seat travel. Conclusions: Effective interventions to increase the proportion of children travelling in the rear seat should address parents' experiences of pressure to relax seating rules and risk perception, as well as provide strategies that support sound parental safety decisions.